Survival and Persistence of Foodborne Pathogens in Manure-Amended Soils and Prevalence on Fresh Produce in Certified Organic Farms: A Multi-Regional Baseline Analysis - Ramos, Thais De Melo; Jay-Russell, Michele T.; Millner, Patricia D.; Baron, Jerome Nicholas; Stover, James; Pagliari, Paulo; Hutchinson, Mark; Lilley, Jason; Rowley, Nicholas; Haghani, Viktoria; Aminabadi, Peiman; Kenney, Annette; et al. (Frontiers in Sustainable Food Systems, 2021)
Biological soil amendments of animal origin (BSAAOs), including untreated (e.g., raw or aged manure, or incompletely composted manure) and treated animal products (e.g., compost), are used for crop production and as part of soil health management. Application of BSAAO's must be done cautiously, as raw manure commonly contains enteric foodborne pathogens that can potentially contaminate edible produce that may be consumed without cooking. USDA National Organic Program (NOP) certified production systems follow the 90-or 120-day interval standards between applications of untreated BSAAOs and crop harvest, depending on whether the edible portions of the crops are in indirect or direct contact with the soil, respectively. This study was conducted to evaluate the survival of four foodborne pathogens in soils amended with BSAAOs and to examine the potential for bacterial transfer to fresh produce harvested from USDA NOP certified organic farms (19) from four states. Only 0.4% (2/527) of produce samples were positive for L. monocytogenes. Among the untreated manure and compost samples, 18.0% (42/233) were positive for at least one of the tested and culturable bacterial foodborne pathogens. The prevalence of non-O157 STEC and Salmonella in untreated manure was substantially > that of E. coli O157:H7 and L. monocytogenes. Of the 2,461 soil samples analyzed in this study, 12.9% (318) were positive for at least one pathogen. In soil amended with untreated manure, the prevalence of non-O157 STEC [7.7% (190) and L. monocytogenes (5.0% (122), was > that of Salmonella (1.1% (26)] or E. coli O157 [0.04% (1)]. Foodborne pathogen prevalence in the soil peaked after manure application and decreased significantly 30 days post-application (dpa). However, non-O157 STEC and L. monocytogenes were recovered from soil samples after 90 and 120 dpa. Results indicate that produce contamination by tested foodborne pathogens was infrequent, but these data should not be generalized outside of the specific wait-time regulations for organic crop production and the farms studied. Moreover, other sources of contamination, e.g., irrigation, wildlife, environmental conditions, cropping and management practices, should be considered. This study also provides multi-regional baseline data relating to current NOP application intervals and development of potential risk mitigation strategies to reduce pathogen persistence in soils amended with BSAAOs. These findings contribute to filling critical data gaps concerning occurrence of fecal pathogens in NOP-certified farming systems used for production of fresh produce in different US regions.